First Cut 2 : More Conversations with Film Editors - Oldham, Gabriella (University of California Press, 2012)
First Cut 2: More Conversations with Film Editors presents a new collection of twelve interviews with award-winning film editors who discuss the art and craft of editing in the twenty-first century. As a follow-up to the successful First Cut: Conversations with Film Editors (now celebrating its 20th anniversary), this new volume explores the transition of editing from the age of celluloid to the digital age. These extraordinarily articulate editors share their passion about film, offer detailed practical examples from their films to explain their process as well as their challenges, and imbue.